Seeding Activity-Based Detection Uncovers the Different Release Mechanisms of Seed-Competent Tau Versus Inert Tau via Lysosomal Exocytosis - Tanaka, Yuki; Yamada, Kaoru; Satake, Kyoko; Nishida, Itaru; Heuberger, Matthias; Kuwahara, Tomoki; Iwatsubo, Takeshi (Frontiers in Neuroscience, 2019)
The pathological aggregation of tau characterizes a set of neurodegenerative diseases collectively referred to as tauopathies. Recent studies using cellular and animal models have suggested that tau pathology progresses by trans-cellular propagation. The process of propagation is mediated by certain species of extracellular tau, which are taken up by recipient cells and serve as a seed for tau aggregation. Tau propagation is currently one of the most active areas of research in dementia. Previous efforts to identify the specific tau molecules involved in propagation have suggested that multiple forms of tau with different molecular weights derived from recombinant tau or brain lysates exert seeding activity. Nonetheless, the molecular characteristics of the “extracellular” seed-competent tau as well as its release mechanisms remain to be elucidated. Given that tau is physiologically released into the extracellular space, it is critical to distinguish seed-competent tau from normal monomeric tau. Utilizing biosensor cells expressing P301S mutant tau fused to CFP/YFP, here we discriminated between seed-competent tau and inert monomer tau released from HEK293 cells. By analyzing the size-exclusion fractions of the media, we found that seed-competent tau was enriched in high molecular weight fractions of >2,000 kDa, while the majority of soluble tau in the media positively detected by ELISA was in low molecular weight fractions. We also found that lysosomal stress not only increased Ca2+-dependent release of seed-competent tau but also altered its molecular size. Inhibiting lysosomal exocytosis specifically decreased release of seed-competent tau without influencing total tau. These data underscore the differential response of seed-competent tau and inert tau to lysosomal stress and indicates the presence of distinct release mechanisms via lysosomes.